(untitled) (Lafia Journal of Scientific and Industrial Research, 2026)
The presence of multidrug resistant (MDR) bacteria in water poses severe health challenges because of high risks of infection and limited treatment choices. This study was conducted to determine the antibacterial activity of Aframomum melegueta and Ocimum gratissimum on MDR bacteria from drinking water. Membrane filtration, Gram staining and biochemical test were used to analyse water samples and identify the Bacterial isolates. The susceptibility test and minimum inhibitory concentration carried out employed the agar well diffusion method and microbroth dilution technique respectively. The bacteria isolated includes Escherichia coli, Salmonella sp. Staphylococcus aureus, Klebsiella sp. and Proteus sp. The physical and chemical evaluation of the water indicates that acidic pH numbers fall below WHO standard and turbidity levels was above the standard. Phytochemical parameters of both plants reveal the presence of saponins, tannins, flavonoids, glycosides, and alkaloids. The susceptibility test result shows that Escherichia coli had the highest susceptibility to the extracts of O. gratissimum, with zones of inhibition of 27.5 ± 3.5 mm and 23.5 ± 2.8 mm respectively at 100 mg/mL, while Klebsiella spp. showed the least susceptibility. Hot and cold extracts of A. melegueta demonstrated lower antimicrobial activity, with highest diameter zone of inhibition observed against E. coli (12.5 ± 0.7 mm at 100 mg/mL). The result from the present study revealed that hot and cold extracts of O. gratissimum exhibited better antimicrobial activity compared to A. melegueta against MDR bacteria isolated from drinking water sources. Routine surveillance of antimicrobial resistance in environmental water sources is highly recommended.